Chinese damselflies of the genus Coenagrion (Zygoptera: Coenagrionidae) - Yu, Xin; Bu, Wenjun (Zootaxa, 2011)
We review and update species of Coenagrion recorded from China, including distributional information. A key to the males is provided including figures of the genital ligula and caudal appendages. A distributional record of Coenagrion armatum is excluded from China. Coenagrion bifurcatum Zhu & Ou-yan, 2000, is assigned as a junior synonym of Coenagrion johanssoni (Wallengren, 1894). Coenagrion chusanicum Navás, 1933 is assigned as a junior synonym of Paracercion hieroglyphicum (Brauer, 1865). Coenagrion dorothea Fraser, 1924 is newly combined as Paracercion dorothea (Fraser, 1924) comb. nov. Coenagrion impar Needham, 1930 and Cercion yunnanensis Zhu & Han, 2000 are both treated as junior synonyms of Paracercion dorothea. Coenagrion holdereri (Förster, 1900) is redescribed here based on fresh specimens.